Physician Perceptions and Beliefs about Generating and Providing a Clinical Summary of the Office Visit - Emani, S.; Ting, D.Y.; Healey, M.; Lipsitz, S.R.; Ramelson, H.; Suric, V.; Bates, D.W. (Applied Clinical Informatics, 2015)
Background: A core measure of the meaningful use of EHR incentive program is the generation and provision of the clinical summary of the office visit, or the after visit summary (AVS), to patients. However, little research has been conducted on physician perceptions and beliefs about the AVS.Objective: Evaluate physician perceptions and beliefs about the AVS and the effect of the AVS on workload, patient outcomes, and the care the physician delivers.Methods: A cross-sectional online survey of physicians at two academic medical centers (AMCs) in the northeast who are participating in the meaningful use EHR incentive program.Results: Of the 1 795 physicians at both AMCs participating in the incentive program, 853 completed the survey for a response rate of 47.5%. Eighty percent of the respondents reported that the AVS was easy (very easy or quite easy or somewhat easy) to generate and provide to patients. Nonetheless, more than three-fourths of the respondents reported a negative effect of generating and providing the AVS on workload of office staff (78%) and workload of physicians (76%).Primary care physicians had more positive beliefs about the effect of the AVS on patient outcomes than specialists (p<0.001) and also had more positive beliefs about the effect of the AVS on the care they delivered than specialists (p<0.001).Conclusions: Achieving the core meaningful use measure of generating and providing the AVS was easy for physicians but it did not necessarily translate into positive beliefs about the effect of the AVS on patient outcomes or the care the physician delivered. Physicians also had negative beliefs about the effect of the AVS on workload. To promote positive beliefs among physicians around the AVS, organizations should obtain physician input into the design and implementation of the AVS and develop strategies to mitigate its negative impacts on workload.Citation: Emani S, , Ting DY, Healey M, Lipsitz SR, Ramelson H, Suric V, Bates DW. Physician perceptions and beliefs about generating and providing a clinical summary of the office visit. Appl Clin Inform 2015; 6: 577–590http://dx.doi.org/10.4338/ACI-2015-04-RA-0043
Keywords: Electronic health records; meaningful use; after visit summary; physicians; beliefs; evaluation